2012
DOI: 10.1155/2012/716023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genotoxic and Cytotoxic Hazards in Brain and Bone Marrow Cells of Newborn Rats Exposed to Extremely Low-Frequency Magnetic Field

Abstract: The present study aimed to evaluate the association between whole body exposure to extremely low frequency magnetic field (ELF-MF) and genotoxic , cytotoxic hazards in brain and bone marrow cells of newborn rats. Newborn rats (10 days after delivery) were exposed continuously to 50 Hz, 0.5 mT for 30 days. The control group was treated as the exposed one with the sole difference that the rats were not exposed to magnetic field. Comet assay was used to quantify the level of DNA damage in isolated brain cells. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The activity of antioxidant enzymes increased in young and decreased in old animals. This observation was supported by the results of Rageh et al [43], who exposed 10-day-old rats to a continuous 50 Hz, 0.5 mT electromagnetic field for 30 days. They found that EMF exposure resulted in higher MDA concentration and SOD activity and increased the rate of oxidative damage to cellular DNA.…”
Section: Discussionsupporting
confidence: 73%
“…The activity of antioxidant enzymes increased in young and decreased in old animals. This observation was supported by the results of Rageh et al [43], who exposed 10-day-old rats to a continuous 50 Hz, 0.5 mT electromagnetic field for 30 days. They found that EMF exposure resulted in higher MDA concentration and SOD activity and increased the rate of oxidative damage to cellular DNA.…”
Section: Discussionsupporting
confidence: 73%
“…Biological effects modulated by EMFs include, but are not limited to, cell migration, cell proliferation and differentiation, cytokine modulation, the expression of growth factors, and nitric oxide signaling [7,8,9,10,11,12]. Potential negative effects of ELF-EMFs have been shown in earlier studies, which demonstrated an increased risk of disease promotion and progression in childhood cancer, breast cancer, neoplastic development, neurodegenerative diseases, and in fertility and cardiovascular disorders [13,14,15,16]. However, these experimental studies did not provide convincing evidence for a relationship between exposure to ELF-EMF and disease development.…”
Section: Introductionmentioning
confidence: 99%
“…Since the energy transmitted by low frequency magnetic or electromagnetic fields is not high enough to affect chemical bonds, it is generally accepted that ELF fields are not capable of damaging the DNA directly [ 9 ]. Nevertheless, a number of studies have reported on changes on DNA integrity after exposure to 50 Hz MF at flux densities ranking 0.1–1 mT [ 10 , 11 , 12 ] and several hypotheses have been put forward on how ELF fields might indirectly affect DNA structure [ 13 , 14 , 15 ]. For instance, it has been proposed that if MF exert a tumorigenic effect, they would do through tumor growth promotion, involving, among other mechanisms, a mitogenic-induced signal transduction that causes the cell to proliferate.…”
Section: Introductionmentioning
confidence: 99%